VD_FINDINFO Jug / 2014 / 88 vom 30. Oktober 2013 - VD Tribunal cantonal (2013)
VACANCES, HEURES DE TRAVAIL SUPPLÉMENTAIRES, RÉSILIATION ABUSIVE, DROIT AU SALAIRE | 319 CO, 321c CO, 329d al. 1 CO, 336 al. 1 CO